2022
DOI: 10.1136/bjophthalmol-2021-320121
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for epiretinal membrane in eyes with primary rhegmatogenous retinal detachment that received silicone oil tamponade

Abstract: Background/aimsThis study investigated the risk factors for epiretinal membrane (ERM) in eyes with primary rhegmatogenous retinal detachment (RRD) that received silicone oil (SO) tamponade.MethodsThis retrospective analysis included 1140 patients (1140 eyes) with RRD who underwent primary vitrectomy and SO tamponade. The prevalence of ERM was estimated and possible risk factors (eg, type 2 diabetes, proliferative vitreoretinopathy (PVR), SO tamponade time (SOTT), photocoagulation, vitreous haemorrhage, choroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Both reviews included patients with complex cases with advanced PVR, requiring retinectomy and use of silicone oil. We decided to exclude studies involving these patients, as both advanced PVR and silicone oil are known risk factors for postoperative ERM formation 15 , 18 and their inclusion could lead to overestimation of the effects of the intervention. In addition, recent studies have suggested that the current classification of PVR 21 has important limitations: early stages (A or B) are commonly under-reported, there is a certain level of subjectivity and correct classification remains complex in some cases 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both reviews included patients with complex cases with advanced PVR, requiring retinectomy and use of silicone oil. We decided to exclude studies involving these patients, as both advanced PVR and silicone oil are known risk factors for postoperative ERM formation 15 , 18 and their inclusion could lead to overestimation of the effects of the intervention. In addition, recent studies have suggested that the current classification of PVR 21 has important limitations: early stages (A or B) are commonly under-reported, there is a certain level of subjectivity and correct classification remains complex in some cases 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for postoperative ERM formation are long axial length, the use of 20G (rather than 23 or 25G) ports, use of silicone oil, high photocoagulation energy, type 2 diabetes and preoperative proliferative vitreoretinopathy (PVR) 15 , 18 . The benefit of ILM peeling should be evaluated by taking into account the varying degrees of surgical complexity and different surgical techniques as well as differences in preoperative macular status (on/off; preoperative ERM) and the rate of PVR.…”
Section: Introductionmentioning
confidence: 99%
“…ERM was found more frequently in eyes with giant tears, likely due to the higher chances of RPE dispersion and vitreous hemorrhage in these cases [ 25 ]. ERM was also associated with the use of large-caliber vitrectomy probes (23-gauge), which may be related to the complexity of the cases operated using these probes [ 26 ]. ORF was more frequently observed in association with ERM, suggesting that epiretinal traction could impede retinal relaxation after reattachment, favoring ORF formation.…”
Section: Discussionmentioning
confidence: 99%
“…A key step in achieving this is to identify patients at high risk for PVR development because they would benefit the most. Previous studies have reported multiple clinical risk factors for PVR through univariate and multiple regression analyses, including preoperative PVR, preoperative vitreous hemorrhage, silicone oil (SO) tamponade, large retinal hiatus, choroidal detachment (CD), and excessive cryotherapy [7][8] . However, the results of these studies were frequently inconsistent and contradictory.…”
Section: Introductionmentioning
confidence: 99%